ASUHAN KEPERAWATAN KELUARGA PADA KELUARGA TN. R KHUSUSNYA TN. R DENGAN HIPERTENSI DI KAMPUNG SASAK KECAMATAN LIMOKOTA DEPOK - Novita Fitriani (2023)
Hypertension is a condition in which on repeated examinations a person's systolic blood pressure exceeds ≥ 140 mmHg and his diastolic blood pressure ≥ 90 mmHg. Hypertension is also the biggest cause of cardiovascular disease that makes sufferers experience despair including heart failure, heart attack, kidney disease, and stroke whose prevalence continues to grow. This study aims to implement family nursing care for patients with hypertension. This research uses a case study method related to family nursing and is focused on family members with hypertension in Mr.R's family, especially Mr.R. The results of the research that has been conducted on Mr.R's family, especially Mr.R, found that Mr.R experiences ineffective health maintenance problems related to the family's inability to care for family members with hypertension health problems and injury agent problems. The conclusion of the case in Mr.R is that nursing problems can be overcome according to proper and correct family nursing care. Suggestions that can be given are to continue to provide mutual motivation and encouragement that remind each other to care for and overcome families suffering from hypertension.